2003
DOI: 10.1210/jc.2003-030093
|View full text |Cite
|
Sign up to set email alerts
|

Association of a Rare Thyroglobulin Gene Microsatellite Variant with Autoimmune Thyroid Disease

Abstract: Genetic and environmental factors contribute to the development of Graves' disease and Hashimoto's thyroiditis. These diseases, although clinically distinct, share many immunological and histological features. Susceptibility genes for autoimmune thyroid disease (AITD) have been investigated, although only the human leukocyte antigen and cytotoxic T lymphocyte-associated antigen-4 gene regions have been consistently associated with disease. Recent data, however, have shown linkage and association of chromosome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
49
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(59 citation statements)
references
References 36 publications
9
49
1
Order By: Relevance
“…Moreover, association studies showed a significant association of Tgms2 with AITD (23; P ϭ 0.004). These results have been replicated recently in a U.K. dataset (25). As in our study, the U.K. study also showed a significant association between Tgms2 and AITD (P Ͻ 0.001).…”
supporting
confidence: 91%
“…Moreover, association studies showed a significant association of Tgms2 with AITD (23; P ϭ 0.004). These results have been replicated recently in a U.K. dataset (25). As in our study, the U.K. study also showed a significant association between Tgms2 and AITD (P Ͻ 0.001).…”
supporting
confidence: 91%
“…Indeed, this mechanism has been shown to play a major role in the etiology of Type 1 diabetes [56]. Thyroglobulin (Tg) gene is the first thyroid-autoantigen gene to be shown to confer susceptibility for AITD [57][58][59]. Similar to results reported in Caucasian population, a significant association between the 330bp/352bp genotype of Tgms2 and HT was found in a large cohort of Japanese AITD patients [55].…”
Section: Serum Igg4 and Its Thyroid Originsupporting
confidence: 57%
“…4 Indeed, additional putative GD susceptibility genes have been recently identified, including CTLA-4, [31][32][33][34] CD40, 35,36 and thyroglobulin. [37][38][39] Patients and methods…”
Section: Discussionmentioning
confidence: 99%